Perkembangan Hukum Tata Negara Dalam Menegaskan Prinsip Negara Hukum Pada Praktik Ketatanegaraan Modern - Eni Wahyuni; Eka Safitri; Iswandi Andika (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2025)
This study aims to analyze the development of constitutional law in affirming the principle of the rule of law in modern constitutional practice. The main focus of the study is directed at the shift in the function of constitutional law from merely regulating the structure and authority of state institutions to a normative instrument that guarantees the limitation of power, protection of citizens' rights, and accountable governance. This study uses a normative juridical approach by examining legal doctrine, legislation, and the development of constitutional thought in the context of a modern rule of law. The results of the study indicate that consistency between constitutional norms and constitutional practice is a determining factor in the effectiveness of the rule of law principle. The constitution serves as the primary foundation in building the legitimacy of power and as a means of controlling potential abuse of authority. However, strong legal norms will not be effective without the support of independent institutions, functioning oversight mechanisms, and a legal culture that upholds the rule of law. This study also finds that the dynamics of modern constitutional law, including the digitalization of government and the increasing complexity of state administration, demand adaptive and responsive reform of constitutional law. The study's conclusion confirms that strengthening the principle of the rule of law can only be achieved through the development of constitutional law that is sustainable, systematic, and oriented towards the values of justice and the public interest. Such constitutional law is the main foundation for realizing modern constitutional practices that are democratic, transparent and responsible.